Promotion of nitric oxide production: mechanisms, strategies, and possibilities - Gonzalez, Marcos; Clayton, Sarah; Wauson, Eric; Christian, Daniel; Tran, Quang-Kim (Frontiers in Physiology, 2025)
The discovery of nitric oxide (NO) and the role of endothelial cells (ECs) in its production has revolutionized medicine. NO can be produced by isoforms of NO synthases (NOS), including the neuronal (nNOS), inducible (iNOS), and endothelial isoforms (eNOS), and via the non-classical nitrate-nitrite-NO pathway. In particular, endothelium-derived NO, produced by eNOS, is essential for cardiovascular health. Endothelium-derived NO activates soluble guanylate cyclase (sGC) in vascular smooth muscle cells (VSMCs), elevating cyclic GMP (cGMP), causing vasodilation. Over the past four decades, the importance of this pathway in cardiovascular health has fueled the search for strategies to enhance NO bioavailability and/or preserve the outcomes of NO’s actions. Currently approved approaches operate in three directions: 1) providing exogenous NO, 2) promoting sGC activity, and 3) preventing degradation of cGMP by inhibiting phosphodiesterase 5 activity. Despite clear benefits, these approaches face challenges such as the development of nitrate tolerance and endothelial dysfunction. This highlights the need for sustainable options that promote endogenous NO production. This review will focus on strategies to promote endogenous NO production. A detailed review of the mechanisms regulating eNOS activity will be first provided, followed by a review of strategies to promote endogenous NO production based on the levels of available preclinical and clinical evidence, and perspectives on future possibilities.